PERTUMBUHAN KUALITAS ROHANI PEMUDA DENGAN MUSIK ROCK DALAM IBADAH - Ferry Wahyu Kartika; Christanto Hadijaya; Trianus Homklom (JOURNAL of THEOLOGICAL STUDENTS, 2021)
Many types of music are used over time, one of which is rock music, this music is considered dark music, its use is associated with negative things such as drunkenness and even drugs, this is because this type of music brings a flow of enthusiasm that is extraordinary for the listener. The conclusion obtained from this research activity is that rock music can improve spiritual quality. This uplifting song contains Bible verses which give a new hope to the listener's heart. In this study the authors used qualitative research methods. Qualitative research method is a type of research whose findings are not obtained through statistical procedures or other forms of calculation and seeks to understand and interpret the meaning of an event of human behavior interaction in certain situations according to the researcher's own perspective.